Otimização do processo de secagem de concretos refratários - Bezerra, Breno Parente (Universidade Federal de São Carlos, 2020)
The drying step of hydraulic-bonded refractory castables is usually carried using conservative and long heating schedules, in order to preserve the microstructure of dense ceramic linings and inhibit explosive spalling risks, due the steam pressurization resulting from the intense water vapor release observed 110°C. Therefore, alternatives to minimize pressurization and/or to enhance the refractories’ explosion resistance may lead to significant energy savings and lower downtime of industrial processes. In this context, this work aimed to evaluate additives that are able to modify the castables’ permeability and prevent their explosion when exposed to fast drying schedules. Commercial additives (Emsil-Dry - ED and RefPac Mipore 20 - MP), alternatives ones (aluminum lactate - LA and calcium lactate - LC) and low melting point polymeric fibers (PP – polypropylene, PLA – polylactic acid, EVA – copolymer ethylene vinyl acetate, and PCL - polycaprolactone) were selected as drying agents. High-alumina castable formulations (with and without additives) containing calcium aluminate cement (CAC) or hydratable alumina (AB) have been designed according to the Andreasen packing model and, subsequently, extensive experimental tests (flowability, cold flexural strength, apparent porosity, permeability measurements, explosion resistance tests, etc.) were carried out to infer the properties and performance of such materials. The obtained results showed that MP, LA or LC additives change the hydration sequences of the used binders (CAC or AB) and that the performance of the polymeric fibers was improved by oxidative effects and their morphological transformations during heating. Except PLA-fibers, the other selected additives (ED, MP, LA, LC, PP, PCL, or EVA) were effective in adjusting the microstructure of CAC-bonded castables. On the other hand, AB-bonded refractory compositions exhibited high explosion resistance by adding MP, PP-fibers, or blends of LA+CAC or LC+CAC.
Optimization of the drying process of refractory castables
Keywords: Secagem; Aditivos de secagem; Permeabilidade; Ligantes hidráulicos; Concretos refratários; Drying behavior; Drying additives; Permeability; Hydraulic binders; Refractory castables; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA::MATERIAIS NAO METALICOS